Formation of high-quality SiC(0001)/SiO2 structures by excluding oxidation process with H2 etching before SiO2 deposition and high-temperature N2 annealing. (12th November 2020) - Tachiki, Keita; Kaneko, Mitsuaki; Kobayashi, Takuma; Kimoto, Tsunenobu
Abstract: We formed SiC/SiO2 structures by various procedures that excluded an oxidation process. We found that a SiC/SiO2 interface with a low interface state density near the conduction band edge of SiC ( D it ∼ 4 × 10 10 cm −2 eV −1 at E c −0.2 eV) is obtained for a fabrication process consisting of H2 etching of the SiC surface, SiO2 deposition, and high-temperature N2 annealing. D it is rather high without H2 etching, indicating that etching before SiO2 deposition plays a significant role in reducing D it . The key to obtaining low D it may be the removal of oxidation-induced defects near the SiC surface.